Implications of Legal Positivism on Cybercrime Law Enforcement in Indonesia in the Case of the Hacking of the Mojokerto City Government Website - Sukirno; Lisdiyono, Edy; Mulyani, Sri (International Journal of Criminology and Sociology, 2021)
The existence of legal positivism that prioritizes legal certainty is expected to resolve various cybercrime criminal cases. One of them happened in the case of the Mojokerto City Government site hacking. The case has troubled the community, especially the city government of Mojokerto. The research method uses normative juridical research with a legal approach, concepts and collects primary legal materials in hacking rules and information technology in cybercrime crime. The study results found that the existence of legal positivism in the crime of cybercrime positions the law as statutory regulation and law as an order containing sanctions. In-Law No. 19 of 2016 concerning amendments to Law No. 11 of 2008 concerning Electronic Information and Transactions contains orders and prohibited actions. The actions taken by the suspect are deemed unfair if there are no sanctions or punishments because, according to legal positivism, justice that is legality (statutory regulation) is justice that prioritizes legal certainty. The law in force in article 46 paragraph 3 of Law No. 19 of 2016 concerning Amendments to Law No. 11 of 2008 concerning Electronic Information and Transactions must be imposed on the suspect in the Mojokerto City government website hacking case.